Ecto-Nucleotidase Inhibitors: Recent Developments in Drug Discovery - Baqi, Younis (Mini Reviews in Medicinal Chemistry, 2015)
Ecto-nucleotidases are nucleotide metabolizing enzymes that are divided into four different families; nucleoside triphosphate diphosphohydrolases (NTPDases), ecto-5′-nucleotidase (ecto-5′-NT), nucleotide pyrophosphatase/phosphodiesterases (NPPs), and alkaline phosphatases (APs). These enzymes are responsible for the hydrolysis of nucleotidases (nucleoside 5′-triphosphates, 5′-diphosphates and 5′-monophosphates). Ecto-nucleotidases modulate P1- and P2-receptor-mediated signaling. Alterations in extracellular nucleotide and adenosine level can increase or decrease P1 and P2 activity. Potent and selective ligands for certain ectonucleotidase are important as pharmacological tools to investigate the (patho)physiological roles of these enzymes. Furthermore, such ligands are required to study their potential as novel drugs, e.g., as immunomodulatory agents, for the treatment of cancer, cardiovascular or central nervous system disorders. Hence, this review aims to provide an overview of ecto-nucleotidases inhibitors developed so far.
Keywords: platelet